2018
DOI: 10.18356/6f73a472-en
|View full text |Cite
|
Sign up to set email alerts
|

Who borrows to accumulate assets? Class, gender and indebtedness in Ecuador’s credit market

Abstract: This article examines the propositions that wealth inequality supports credit market segmentation and that the financial system may reproduce economic inequality. Specifically, we discuss how the sources of credit and the purposes of borrowing may help perpetuate inequality. In Ecuador, the asset-poor are more likely than the asset-rich to borrow from the informal sector for expense purposes and to have higher debt-to-net-wealth ratios. We also investigate the correlates of borrowing by men and women to acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Despite efforts to expand access to credit by the provincial government and credit cooperatives (Hollenstein and Ospina Peralta ), access to credit is still largely limited to family networks and remittance income for those with relatives abroad. This is true in general for the lower quintiles of Ecuadorean society (Deere and Catanzarite ) and stymies the development efforts these families would pursue if given the chance. The Correa political economy, with its focus on visible infrastructure and lack of attention to preferred lines of credit for smallholders or any significant redistribution of assets (Larrea and Greene ), resulted in an uneven accumulation of the different forms of community capital.…”
Section: Discussion: From Buen Lugar To Active Citizenshipmentioning
confidence: 99%
“…Despite efforts to expand access to credit by the provincial government and credit cooperatives (Hollenstein and Ospina Peralta ), access to credit is still largely limited to family networks and remittance income for those with relatives abroad. This is true in general for the lower quintiles of Ecuadorean society (Deere and Catanzarite ) and stymies the development efforts these families would pursue if given the chance. The Correa political economy, with its focus on visible infrastructure and lack of attention to preferred lines of credit for smallholders or any significant redistribution of assets (Larrea and Greene ), resulted in an uneven accumulation of the different forms of community capital.…”
Section: Discussion: From Buen Lugar To Active Citizenshipmentioning
confidence: 99%
“…Mascia and Rossi (2017) confirmed the existence of different borrowing conditions for women and men entrepreneurs related to interest rates, fees, and commissions across 11 European countries. In Ecuador, having income-generating employment increases the probability of women borrowing by 14.2% (Deere & Catanzarite, 2018). However, as women face specific barriers to participating in the labour market, their borrowing possibilities are limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An econometric analysis of access to asset loans for Ecuador -where these are predominantly from the formal sector-found that the likelihood of having an asset loan for both men and women was positively associated with having a formal bank account (Deere and Catanzarite 2017). Earning an income increased the likelihood of having an asset loan for women, but not for men, while being a member of a social network increased it only for men.…”
Section: Credit For Asset Accumulationmentioning
confidence: 99%
“… See Grown et al (2015: Table 9), for the distribution of all formal and informal loans by specific sources.24 On Ghana, see Joseph KimosAdjei, Thankom Arun and Farhad Hossain (2009); on Ecuador, see Carmen DianaDeere and Zachary Catanzarite (2017).25 This analysis is based on the study of the web pages of the main private banks as well as interviews.…”
mentioning
confidence: 99%